Efisiensi desalinasi air laut dengan menggunakan konsentrasi reflektor parabolik - E.Y. Tae; B.V. Tarigan; M. Jafri (Universitas Mataram, 2024)
Water is very important for the life of living things, many countries in the world are experiencing a clean water crisis. The total global water reserve is less than 1.4 billion km3, of which about 97.5% is in the oceans and the remaining 2.5% is fresh water contained in the atmosphere, ice mountains and groundwater. Desalination is generally the process of removing salt from seawater or saltwater. Desalination of seawater and brackish water can be utilized to increase the availability of clean water. Two types of desalination techniques used can be classified into phase change (heat) and membrane. desalination techniques with phase change processes are processes that utilize changes in a substance under certain temperature conditions. While desalination techniques with membrane processes are processes that focus on filtering a substance accurately. Comparison of desalination efficiency between the three materials in different days is the flanel sheet material, the goni and the combination of flanels and goni. Flanel leaf material has the highest efficiency value on the 1st day with a presentation of 57,71% while the lowest one has a value of 32,24%. Then on the 2nd day the most efficient value is 45,32%, while the least value is 0%. In the first day goni material has a highest efficacy value with a presentation of 34,56%, and a lowest value with 0%. Then the second day trial with the same material has its highest effectiveness value with the presentation of 41,44%, and the lower value with 0%.